(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The impact of love language on self-esteem and relationship satisfaction of a long-term partner was particularly interesting; people could view it scientifically as where the pair continues to engage in a loving and healthy understanding of how to recognize their partner’s expression of love after numerous years of relationship. Listening to one another and trying to understand how each other feels. Self-esteem and Satisfaction in Relationships are important aspects of life and can determine relationship satisfaction. In close relationships, satisfaction is defined as the subjective attitude (satisfaction) and affective experience (happiness) in evaluating one’s relationship. This study aimed to determine the Impact of Love language on the self-esteem and relationship satisfaction of partners in San Bartolome Quezon City. A purposive sampling technique was used, which included 50 respondents from Barangay San Bartolome. This study utilized the Quantitative method, using a validated questionnaire of frequency and percentage distribution. After gathering data and tabulating the results, it was found that there is no significant impact of love language on the self-esteem and relationship satisfaction of partners in San Bartolome.